2017
DOI: 10.4012/dmj.2016-290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various etching protocols on the flexural properties and surface topography of fiber-reinforced composite dental posts

Abstract: The purpose of this study was to evaluate the flexural properties and surface topography of fiber posts surface-treated with various etching protocols. Seventy each of three types of fiber posts: RelyX Fiber Post, Tenax Fiber Trans, and D.T. Light-Post Illusion X-Ro, were randomly divided into 7 groups: no surface treatment, surface treated with hydrofluoric acid (HF) 4.5% for 60 s, HF 4.5% for 120 s, HF 9.6% for 15 s, HF 9.6% for 60 s, HF 9.6% for 120 s, and treated with H2O2 24% for 10 min. The specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…11,34,35 Several studies have been previously carried out to investigate the bond strength of adhesive and fiber post systems. 36,37,38,39,40 Flexural strength of the fiber post may play a significant role in the outcome of postretained restoration. 41 An important factor for fiber post strength could be the type of resinous matrix and the manufacturing process used to promote chemical bond between the fiber and the resin.…”
Section: Discussionmentioning
confidence: 99%
“…11,34,35 Several studies have been previously carried out to investigate the bond strength of adhesive and fiber post systems. 36,37,38,39,40 Flexural strength of the fiber post may play a significant role in the outcome of postretained restoration. 41 An important factor for fiber post strength could be the type of resinous matrix and the manufacturing process used to promote chemical bond between the fiber and the resin.…”
Section: Discussionmentioning
confidence: 99%
“…The surface treatment with HF showed higher bond strength of CSCs to ber posts than SB and C groups. The HF surface treatment might modify the outer surface layer of the ber post without compromising the strength properties of the post [23,25]. It was observed that HF surface treatment caused some cracks in RP post and the glass bers were exposed in RX post ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that 4 and 9.5% concentrations of hydrofluoric acid exerted similar effects on fiber post durability. However, prolonged exposures, such as 120 s, can deteriorate glass fibers, thus increasing their fragility (Aksornmuang, Chuenarrom, & Chittithaworn, 2017). Micro-push-out adhesion ability of fiber posts increases when 9.5% hydrofluoric acid is applied for 60 s (Cekic-Nagas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%